Pharmaceutical Study of Amavatari Rasa and Rasnadi Guggulu Ayurvedic Formulations. - Sharma, DK; Charak, Sandeep; Sharma, Karunanidhi; Suresh, Parimi (International Research Journal of Ayurveda & Yoga, 2022)
It is a system where principles of living and treatment are described in codified form. Rasashastra and Bhaishajya kalpana is a branch of Indian Alchemy and Iatrochemistry. In this branch number of herbo-mineral and purely herbal formulations are mentioned with wide range of dosage forms. It is not only a science of drug manufacturing but also the science of selection, identification, prevention and standardization. A good quality of products assures the anticipated results. The pharmaceutical preparations when prepared with proper scientific approach it can prove to be a boon for patients. Amavatari rasa and Rasnadi guggulu are amongst the important preparations, which have been mentioned in well-known rasa text Brihat yog tarangini and Bhaishjya ratnavali. Pharmaceutical study involves preparation of Amavatari Rasa and Rasnadi Gugglu according to classical method. All the raw materials were procured from the Pharmacy of N.I.A, Jaipur and Pharmaceutical procedures were carried out in the department of Rasa Shastra and Bhaishajya Kalpana, NIA Jaipur.